Peroxymonosulfate activation by concave porous S/N co-doped carbon: Singlet oxygen-dominated non-radical efficient oxidation of organics. Issue 3 (June 2022) - Chen, Yuyu; Liang, Qianwei; Deng, Yuhui; Bin, Yuliang; Wang, Tao; Luo, Hanjin
Abstract: Developing high-efficient, low-cost and environmentally friendly catalysts is essential for activating peroxymonosulfate (PMS) but remains a challenge. Recently, novel catalysts of transition metal-nitrogen co-doped carbon materials, especially Fe-N-C, have attracted much attention due to their superior performance for PMS activation. Herein, FeSO4 and ZnSO4 were added during the synthesis of ZIF-8, obtained concave N, S co-doped iron-based carbon materials (Fe-S@NC) with mesoporous structure through high-temperature pyrolysis. This porous carbon material with a depressed surface not only promoted the exposure of active sites, but also accelerated mass transfer. The synergistic effect of Fe atoms and heteroatoms significantly enhanced the activation ability of the material to PMS. Benefiting from these advantages, only 2 mg/L Fe-S1 @NC and 0.5 mM PMS was required to achieve the rapid degradation of acetaminophen (ACT) (99.7%, 0.7290 min -1 ). Besides, the activation system has a wide pH adaptability and low leaching iron concentration. Then the reaction mechanism of Fe-S1 @NC/PMS system was investigated by quenching experiments and electron paramagnetic resonance technique (EPR), it was proposed that singlet oxygen ( 1 O2 ) was the primary reactive species responsible for the degradation of ACT. This study provides new insight for the design of carbon catalysts in advanced oxidation field. Graphical Abstract: ga1 Highlights: Concave porous N, S co-doped iron-based carbon materials were synthesized by simple pyrolysis process. Fe-S1 @NC exhibits excellent PMS activation performance. Fe, S and N have a synergistic effect on the degradation of ACT in Fe-S1 @NC/PMS system. 1 O2 was verified to be the major ROS responsible for ACT degradation.